A WeChat-Based Mobile Platform for Perioperative Health Education for Gastrointestinal Surgery - Ying Li; Xiao-hui Cheng; Wen-ting Xu; Li-ping Tan; Xiao-jun Gou (Emergency Medicine International)
Appropriately instructing and guiding patients before and after surgery is essential for their successful recovery. In recent years, however, the development of the enhanced recovery after surgery (ERAS) protocol has restricted the opportunity for healthcare professionals to spend time with their patients before and after surgery because of efficiency-driven, shortened hospital stay. Here, we embedded health education information of the perioperative period for gastrointestinal surgery on a WeChat-based mobile platform and evaluated the platform through medical staff evaluation, patient volunteer evaluation, and quantitative grading rubric. Clinicians and nurses believed that the mobile platform was attractively designed and easy to navigate, valuable, and adequate for patient health education. The content of health education was embedded into the WeChat-based mobile platform, thereby allowing patients and caregivers to access information at their own pace and enable repeat reading.